Boosting Electrochemical Performance via Extra‐Role of La‐Doped CeO2‐δ Interlayer for “Oxygen Provider” at High‐Current SOFC Operation - Xuan Dong Nguyen; Sang Won Lee; Su Ji Kim; Jungdeok Park; Bonseok Koo; Seok Hee Lee; Shiwoo Lee; Hyung Tae Lim; John T.S. Irvine; Tae Ho Shin (Advanced Science)
Abstract Utilizing rare earth doped ceria in solid oxide cells (SOCs) engineering is indeed a strategy aimed at enhancing the electrochemical devices' durability and activity. Particularly, Gd‐doped ceria (GDC) is actively used for barrier layer and catalytic additives in solid oxide fuel cells (SOFCs). In this study, experiments are conducted with La‐doped CeO2 (LDC), in which the Ce sites are predominantly occupied by La, to prevent the formation of the Ce‐Zr solid solution. This LDC is comparably used as a functional interlayer between the electrolyte and cathode if sintered at lower temperatures to avoid La2Zr2O7 impurity. In addition, the high substitution of La3+ into the ceria lattice improves the oxygen non‐stoichiometry of LDC, leading to accelerated electrochemical high performance by the additional role of LDC for oxygen supplier capacitance at high current operation. Thus, it is confirmed that the improved SOFC high performance is achieved at the maximum power density (MPD) of ≈2.15 W cm−2 at 800 °C when the optimized LDC buffer layer is hired at the anode‐supported typed‐Samsung's SOFC by lowering the sintering temperature to prevent LDC's impurity reaction.